Some Sharp Results on Coefficient Estimate Problems for Four-Leaf-Type Bounded Turning Functions. (2nd August 2022) - Sunthrayuth, Pongsakorn; Jawarneh, Yousef; Naeem, Muhammad; Iqbal, Naveed; Kafle, Jeevan
Abstract : In this study, we focused on a subclass of bounded turning functions that are linked with a four-leaf-type domain. The primary goal of this study is to explore the limits of the first four initial coefficients, the Fekete-Szegö type inequality, the Zalcman inequality, the Kruskal inequality, and the estimation of the second-order Hankel determinant for functions in this class. All of the obtained findings have been sharp.